-42v+54=-28-8v

Simple and best practice solution for -42v+54=-28-8v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -42v+54=-28-8v equation:



-42v+54=-28-8v
We move all terms to the left:
-42v+54-(-28-8v)=0
We add all the numbers together, and all the variables
-42v-(-8v-28)+54=0
We get rid of parentheses
-42v+8v+28+54=0
We add all the numbers together, and all the variables
-34v+82=0
We move all terms containing v to the left, all other terms to the right
-34v=-82
v=-82/-34
v=2+7/17

You can always share this solution

See similar equations:

| 7x+10=1/3(12x?3)+14x | | 30+2k+5=100 | | 2-6p=-7p | | 8=k-7 | | -5x+3+6x=25 | | 2x•(x+8)+x=180 | | 2x-2=4x/6 | | 7x-1+3x=-1 | | 3(x-2)=5x+8=12 | | 2(6a+3)=66 | | 7-3(5-u)=5(u-4) | | 1/5-3/2=z/10 | | 2^9x+2=16^5x-2 | | 9x=9(x-1) | | -71=-6(4b-4)+5b | | 5/4y-1/3=1/2(3y-1) | | n=1.4-(-6.3) | | 9-3g=14 | | 7y-7/4=-2/3y-4/3 | | 18-2x-14=8x-20/2-2 | | 6+6(3m-6=-138 | | -4(4b+3)=68 | | 4x3x+11=60 | | 11.6+4.1t=6+3.2(t-4) | | .75t+1/8=3/4(t+8) | | b-4÷6=6÷2 | | 4(x-5)+2=4x?18 | | 10+35=-5(8x-9) | | 2(3m+2)=-8 | | 4*(x?5)+2=4x?18 | | x-(4-x)=8 | | 0.8(x-2)+0.5=1-0.2(4-2x)-0.5 | | 10x-4/2+7=5x+5 | | 2(x+0.1)=1.9 | | (3a)^3a=2 | | 12x0.3=40 | | 2a+6=a-7 | | 5x+8-12x=-6x-2x-3 | | 6(2r-1)=-78 | | f(1/2)=2(1/2)+3 | | -(3x+-12)=48 | | -1n+10=3 | | 4(x?5)+2=4x?18 | | x-3/3=-4/1/2X3 | | (1.4)x=8 | | (x-9)^2=49 | | z/3+3=8/3 | | -x÷9=-8 | | ?1+5x?15=?7(?6+8x)+3 | | 8+32y=24 | | 198=68-10x | | 16+2p=20 | | -29=7v+4(-8v-1) | | 3x-3x=17-5 | | x2?125=0 | | -2(x+3)=5(x+1) | | 0=x^2-2x-28 | | 2x+5(18)=6x | | -3(4x+3)+4*6x+1)=43 | | 4r+1=?2r+8 | | -1(3x+-12)=48 | | 116=4(5-6x) | | -5(5x-5)+3=-25x+28 | | 7c+12=-4c(78+12) | | 16x^2-56x+37=0 |